The values of the modern university community (Ukrainian universities in war time) - Korobko, Marharyta (Ukrainian Cultural Studies, 2022)
The last few years have become a challenge for all of humanity. And universities are not the exception. Questions about reforming the modern university education and changing the university community were on the agenda even before the COVID-19 pandemic, but with the need of the distance learning, these questions have become especially acute. How should the modern university look like? To be a platform for providing educational services? Keep the classic Humboldt research university model? What should be the values of the modern university community?Today in Ukraine, the value aspect is fixed in the official documents of universities and scientific institutes, and the observance of academic integrity is regulated by the legislation of Ukraine A university should educate, provoke critical thinking and inspire students to take responsibility for their own life and its activities, be a responsible citizen.With the beginning of a full-scale war in Ukraine, these questions took on an even more bitter flavor, and the very possibility of learning became a huge value. The purpose of the article is to study the values of the university community in modern conditions of uncertainty and crises. The university during the war is the center that helps all its employees, teachers and students to feel part of the community, to receive psychological help, to believe in victory. And after the victory, it will be necessary to think about further modernization and reformation of education.Today, for all Ukrainians, the most important value is our life and freedom, but as professionals in the field of education, we must not forget that the basic values of the academic community are academic freedom and academic integrity. And even in difficult times of war we must not lose faith and hope that if we preserve our basic professional values now, after victory we will be able to rebuild a strong university community that will be not worse, but one of the best in the world.
Keywords: values; university; war; education; ethics